Aplikasi proses dan formulasi face mist dengan penambahan ekstrak bunga telang (Clitoria ternatea L.) sebagai sediaan antijerawat - Asri Widyasanti; Rizka Fauziyah; S Rosalinda (AGROINTEK, 2024)
Face mist preparations are liquid preparations that are sprayed on the face. A natural ingredient that can be added to the anti-acne face mist preparation is butterfly pea (Clitoria ternatea L.) because it contains flavonoid which has the potential as antibacterial. This study aimed to determine the best concentration of butterfly pea extract in an anti-acne face mist preparation. The research method used was laboratory experimental with data analysis using ANOVA, Duncan's test, and descriptive analysis. This study consisted of 4 treatments with varying concentrations of butterfly pea extract namely: treatment A (0%%) treatment B (2%), treatment C (4%) and treatment D (6%). The results showed that all treatments met the quality parameters of appearance, viscosity, spray conditions, inherent resistance properties, and drying time. It did not irritate as well. The best concentration of butterfly pea extract in an anti-acne face mist preparation was 4% because it complied with the requirements for appearance, viscosity, spray conditions, inherent resistance properties, no irritation, stability for 28 days of storage, and had the highest antibacterial activity.